A capacity optimization and scheduling scheme of a multi-energy complementary power station considering energy trading - Zou, Shaokun; Zhang, Ning; Wei, Baoze (Frontiers in Energy Research, 2023)
Digital technology is rapidly advancing, and the resulting digitization of energy is becoming an inevitable trend. Integrating digital technology with energy planning can enable efficient utilization of renewable energy (RE); the fluctuation of RE generation, such as wind and photovoltaic (PV), can be reduced, and the reliability of the power grid can be ensured. A better solution for RE utilization and planning based on digital technology is proposed in this paper. First, an operation mechanism of a multi-energy complementary power station is proposed based on the complementary characteristics of multiple energy sources in the power generation process. The current status and related issues of multi-energy complementary power stations are studied in this paper. Second, a two-layer model of optimization that integrates the complementary features of multiple energy sources and system planning requirements is developed in this paper based on the aforementioned power station operation mechanism. The two layers of the model are nested with each other to realize the operation of the power station. The upper model includes the RE utilization rate and the benefits of the energy storage (ES) system. The lower model includes the operating cost of the power station. The solution model includes the highest utilization rate of RE and the lowest operation cost. Finally, the simulation operation is performed based on the data on a provincial power grid. The model and operation strategy of the multi-energy complementary power station based on digital technology proposed by this paper are verified.